Standardisation of fatwa in Malaysia: management and problems - Nasoha, Zaini; Laluddin, Hayatullah; Mohd Kusrin, Zuliza; Muwazir, Mohd Rizal (American-Eurasian Network for Scientific Information (AENSI), 2012)
In a country where jurisdiction over Islam is placed under state administration, standardization is an aspect that continues to be a formidable challenge. In matters of law, difference in provisions creates complications in its implementation. Similarly, with regards to fatwas difference in fatwas between states on a particular legal problem can create confusion to the public. Although the nature of fatwas in itself allows for differences in opinions and decisions on a legal problem, such difference within a small country like Malaysia can lead to adverse consequences. Hence, this article aims to deliberate upon existing methods for the standardisation of fatwas, looking into the effectiveness of its implementation. For this purpose, several examples of differing fatwas which have been gazetted shall be highlighted. Standardisation methods which will be analysed include the method of administrative action, and the method provided for under the latest version of the State Administration of Islamic Law Enactment. This is in relation to fatwas on issues of national interest.